EFEKTIVITAS LAYANAN BIMBINGAN KELOMPOK TERHADAP PERILAKU SOSIAL PESERTA DIDIK DI SMA N 12 PADANG - Miswar, Dedi; Kasih, Fitria; Nita, Rahma Wira (Bimbingan dan Konseling, 2013)
Problems in the study were students often use profanity in the classroom and outside the classroom, In addition students also said that the group only spent guidance only, boring; make sleepy eyes, and less open in expressing the topics covered in group counseling activities. This study aimed to describe. (1) The effectiveness of group counseling services to students of social behavior seen from the implementation of group counseling services (2) The effectiveness of group counseling services to students of social behavior seen from the benefits of group counseling services. This research is a descriptive study sought to describe the state of things as it is. The population in this study was N 12 High School Students Padang who attended group counseling services totaling 168 people. This study used a sample of 42 people with a purposive sampling technique random sampling. Instruments used to collect data in the form of questionnaires and the data were processed by using a percentage formula. The research findings revealed that the effectiveness of group counseling services to the social behavior of participants in high school students Padang N12 which includes: (1) the effectiveness of group counseling services to students of social behavior seen today considered effective implementation stage 72%. (2) The effectiveness of group counseling services to students of social behavior seen from the benefits of group counseling services classified effectively 75%. Based on the above results the authors suggested that a tutor to better understand group counseling services so as to activity group counseling services hereinafter learners more motivated to follow the activity of group counseling services.